Credit expansion and financial stability in Malaysia - Koong, Seow Shin; Law, Siong Hook; H. Ibrahim, Mansor (Elsevier, 2017)
This study investigated the degree of synchronization between credit expansion and financial stability in Malaysia at aggregated and disaggregated levels. The dynamic factor model and a broad range of macro-financial variables are adopted to construct a financial stability index to measure the stability of the Malaysian financial system. The non-parametric method is subsequently employed to gauge the degree of synchronization between credit and financial stability. The empirical findings indicated a negative synchronization between business credit and financial stability in Malaysia, suggesting that an expansion in business credit would lead to financial instability. The results implied that difficulties will arise in designing policies as business credit expands. On the other hand, there is insufficient evidence to show that increasing household credit has any negative influence on Malaysian financial stability.